Respuesta :

Answer:

A

Step-by-step explanation:

solve for the first variable in one of the equations, they substitute the result into the other equation.

Answer:

C. (-1,0)

Step-by-step explanation:

Given system of inequalities is,

[tex]y\leq -x+3[/tex]

[tex]y\leq x^2-3x[/tex]

Since, the point is called the solution of the above system of inequalities if both inequalities are true for that point,

For point (1,-1),

[tex]-1\leq -1+3[/tex] ( False )

So, (1,-1) can not be the solution,

For point (4,1),

[tex]1\leq -4 + 3[/tex] ( False )

So, (4,1) can not be the solution,

For point (-1,0),

[tex]0\leq -(-1)+3[/tex] ( True )

[tex]0\leq (-1)^2-3(-1)[/tex] ( True )

So, (-1,0) is the solution of the above system,

For point (2,2),

[tex]2\leq -2+3[/tex] ( false )

So, (2,2) can not be the solution,

Hence, Option 'C' is correct.

ACCESS MORE